Pengaruh Digitalisasi dan Teknologi terhadap Profitabilitas pada Perusahaan Multifinance di Bursa Efek Indonesia - Amilia Paramita Sari (Ebisma (Economics, Business, Management, & Accounting Journal), 2026)
This study aims to examine the effect of digitalization and technology on the profitability of multifinance companies listed on the Indonesia Stock Exchange during the period 2021–2025. A quantitative approach using linear regression analysis is employed on four multifinance companies selected through purposive sampling, resulting in 20 observations. Digitalization and technology are proxied by technology-related investment and expense ratios, while profitability is measured using Return on Assets (ROA). The results indicate that digitalization and technology have a positive and significant effect on profitability, with a regression coefficient of 0.731 and a significance level of 0.001. The Adjusted R² value of 0.589 suggests that 58.9% of the variation in profitability can be explained by digitalization and technology. These findings imply that effective digital transformation plays a strategic role in improving financial performance and sustaining competitiveness in multifinance companies.